Implementation of Augmented Reality of Laboratory Building and Room Using Fast Corner Detection Algorithm - Ilhami, Ahmad Mika; Ikhsan, Muhammad (Indonesian Journal of Artificial Intelligence and Data Mining, 2024)
The Laboratory Buildsing is one of the buildings in Campus IV UINSU which is used to carry out practicum activities, many of the lecturers students and the community do not know the location and also the rooms in the Laboratory building. This research aims to make this application can provide convenience for users such as students, lecturers and the public to obtain information about laboratory buildings. In this research, the method used is Marker Based Tracking where application users must scan the marker first in order to see 3D objects from a floor plan and laboratory building. The results of this study in the form of Augmented Reality applications using Android as an operating system, on the marker added with the Fast Corner Detection algorithm aims to speed up real-time computing time with the consequence of reducing the level of accuracy of corner detection.  The conclusion of AR and Fast Corner Detection can be implemented through a scan of the marker, the result obtained is that when scanning the marker a point from the FCD algorithm will appear indicating that the point on this marker is the result of the implementation of the FCD algorithm.